2008
DOI: 10.2172/958415
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of the Hall Effect and Electron Diffusion Region During Magnetic Reconnection in a Laboratory Plasma

Abstract: The Hall effect during magnetic reconnection without an external guide field has been extensively studied in the laboratory plasma of the Magnetic Reconnection Experiment (MRX) [Yamada et al., Phys. Plasmas 4, 1936(1997] by measuring its key signature, an out-of-plane quadrupole magnetic field, with magnetic probe arrays whose spatial resolution is on the order of the electron skin depth. The in-plane electron flow is deduced from out-of-plane magnetic field measurements.The measured in-plane electron flow a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…Similar investigations are conducted in the laboratory with MRX: Yamada et al (2018) observed the high out‐of‐plane velocity (v eM ) at the stagnation point of asymmetric reconnection; Ren et al (2008) observed outflow velocities at 0.11v eA , which are consistent with our measurements.…”
Section: Discussionsupporting
confidence: 91%
“…Similar investigations are conducted in the laboratory with MRX: Yamada et al (2018) observed the high out‐of‐plane velocity (v eM ) at the stagnation point of asymmetric reconnection; Ren et al (2008) observed outflow velocities at 0.11v eA , which are consistent with our measurements.…”
Section: Discussionsupporting
confidence: 91%
“…An interesting observation based on a set of particlein-cell (PIC) simulations is that the maximum Hall-reconnection rate seems universal and is independent of the mechanism that breaks the field lines 20,21 . Observations and laboratory experiments have discovered the Hall field and Hall current associated with fast collisionless magnetic reconnection 10,12 , but no direct experimental or observational evidence has been found to show that the rate is irrelevant to the dissipation mechanism [22][23][24][25] . On the other hand, observations of solar flares found that magnetic reconnection may commonly be turbulent as evidenced by the filamentary structure of magnetic field, non-thermal heating observed in X-ray, and coherent radio emissions that are likely results of electron two-stream instability [26][27][28] .…”
Section: Introductionmentioning
confidence: 99%
“…The Cassak‐Shay formulation has been successfully used to predict the measured reconnection outflow speeds at the magnetopause for a wide range of densities and magnetic field strengths in the magnetosheath and magnetosphere [ Walsh et al ., , ] at various IMF clock angles. In the symmetric‐plasma limit, the Cassak‐Shay equation reduces to the familiar Petschek formula for the fast reconnection rate R ~ 0.1 v A B that has been successfully tested in a variety of computer simulations in the Geospace Environmental Modeling (GEM) reconnection challenge [ Birn et al ., ; Otto , ; Shay et al ., ; Birn and Hesse , ] and tested against dayside reconnection measurements [ Fuselier et al ., ], magnetosheath reconnection measurements [ Phan et al ., ], and collisionless plasma laboratory experiments [ Yamada et al ., ; Ren et al ., ].…”
Section: Introductionmentioning
confidence: 99%